Proceedings of the First International Workshop on Internet-Scale Multimedia Management 2014
DOI: 10.1145/2661714.2661717
|View full text |Cite
|
Sign up to set email alerts
|

Genre-based Analysis of Social Media Data on Music Listening Behavior

Abstract: It is frequently presumed that lovers of Classical music are not present in social media. In this paper, we investigate whether this statement can be empirically verified. To this end, we compare two social media platforms -Last.fm and Twitter -and perform a study on musical preference of their respective users. We investigate two research hypotheses: (i) Classical music fan are more reluctant to use social media to indicate their listing habits than listeners of other genres and (ii) there are correlations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Other analyses could model music discovery or preference by considering specific geographies, musical genres, or even individual users. Large-scale data have been used to address specific musical questions including the long tail in music-related microblogs (Schedl et al, 2014), social media behavior of Classical music fans (Schedl and Tkalčič, 2014), the relationship between musical taste and personality factors (Bansal and Woolhouse, 2015), and Twitter activity around a specific musical event (Iren et al, 2016). Using Shazam data in this way—to address specific musical questions—promises interesting approaches for future research endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…Other analyses could model music discovery or preference by considering specific geographies, musical genres, or even individual users. Large-scale data have been used to address specific musical questions including the long tail in music-related microblogs (Schedl et al, 2014), social media behavior of Classical music fans (Schedl and Tkalčič, 2014), the relationship between musical taste and personality factors (Bansal and Woolhouse, 2015), and Twitter activity around a specific musical event (Iren et al, 2016). Using Shazam data in this way—to address specific musical questions—promises interesting approaches for future research endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the usage of Last.fm data obviously introduces a community bias. For instance, studies showed that listeners of classical music are underrepresented [7], whereas fans of metal and alternative music are overrepresented on the platform [8]. The sample of people present in the dataset at hand (and in general in the LFM-1b set) does therefore not generalize to the population at large.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…In this work, we chose the music platform Last.fm to gather a real-world dataset, since it has been shown to attract users of a wide variety of music tastes [9]. In contrast, existing work commonly makes use of rather small and noisy datasets, typically gathered from Twitter and including a maximum of a few million listening events [6].…”
Section: Related Workmentioning
confidence: 99%